A Bony Mallet Thumb with Interposition of the Nail Plate - Afshar, Ahmadreza; Tabrizi, Ali; Taleb, Hassan (The Surgery Journal, 2021)
Thumb extensor injuries and bony avulsion in the distal phalanx of the thumb are rare compared with other fingers. The most reported complications are infection, nail deformity, joint incongruity, implant failure, recurrent flexion deformity, and residual pain. This report presents a case of 30-year-old man suffering from an injury in the left thumb distal phalanx with a displaced comminuted intra-articular fracture of the distal phalanx of the left thumb. The nail plate was interposed between the dorsal and palmar fragments. The interposition of the nail plate in the bony mallet thumb has not been described before. Surgical treatment and fixation with a 2-mm miniscrew resulted in successful treatment. Clinical suspicion of this complication is of great importance and can affect treatment outcomes.
Keywords: mallet finger; mallet thumb; bony mallet; complications